Right ventricular inflow tract obstruction secondary to metastatic cutaneous squamous cell carcinoma - Hunter, Jonathan Michael (BMJ Publishing Group, 2012)
We report the case of an immunocompetent 83-year-old man with metastatic neoplastic infiltration of the heart from primary squamous cell carcinoma (SCC) of the skin. Death was from cardiopulmonary collapse due to left ventricular failure with features of right ventricular inflow tract obstruction. Metastatic tumours involving the heart rarely originate from cutaneous SCC though have been reported in the literature in both immunocompetent and postrenal-transplant recipient patients. Most involve the pericardium and only rarely the endocardium or the myocardium. While the prognosis is generally poor, palliative radiotherapy may provide significant symptom relief. Cardiac metastases should be considered in patients with advanced cancer, especially when they show cardiac symptoms and signs.